2014
DOI: 10.1002/apj.1849
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of flow in a highly efficient flotation column

Abstract: For the purpose of optimization by numerical analysis, a highly efficient flotation column named cyclonicstatic micro-bubble flotation apparatus, which is widely used in mineral processing, was simulated with computational fluid dynamics to study the distributions of velocity magnitude, pathlines, turbulent intensity, and turbulent kinetic energy under different discretization schemes, turbulence models, and rotational speeds of pump. This simulation was based on the volume of fluid multiphase and multiple ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The realizable k–ε model contains a variable turbulent alternative formula and modifies the transport equation using the turbulent dissipation rate, which is derived from the exact equation for the transport of the mean‐square vorticity fluctuation, hence increasing the calculation accuracy. Gong et al 55 studied the hydrodynamic characteristics of a FCSMC employing the standard, RNG and realizable k–ε models, as shown in Figure 1. The introduction of a turbulence model was found to change the hydrodynamic in the revolving flotation sections and column, and such three k–ε models had numerous differences.…”
Section: Theories Of Computational Fluid Dynamics Numerical Simulation In Studying Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…The realizable k–ε model contains a variable turbulent alternative formula and modifies the transport equation using the turbulent dissipation rate, which is derived from the exact equation for the transport of the mean‐square vorticity fluctuation, hence increasing the calculation accuracy. Gong et al 55 studied the hydrodynamic characteristics of a FCSMC employing the standard, RNG and realizable k–ε models, as shown in Figure 1. The introduction of a turbulence model was found to change the hydrodynamic in the revolving flotation sections and column, and such three k–ε models had numerous differences.…”
Section: Theories Of Computational Fluid Dynamics Numerical Simulation In Studying Flotationmentioning
confidence: 99%
“…The turbulent intensity contours of different turbulence models (face y = 0) reported by Gong et al 55 …”
Section: Theories Of Computational Fluid Dynamics Numerical Simulation In Studying Flotationmentioning
confidence: 99%
“…The MRF model performs steady‐state calculations with a rotating reference frame in the impeller region and a stationary reference frame in the outer region. In this way, the effects of the blade rotation can be explained with the help of the frame of reference, allowing for explicit modelling of the impeller geometry . A number of studies on the impeller configuration have been reported, especially the Ruston turbine which has the lowest power number.…”
Section: Vof Modelmentioning
confidence: 99%
“…In this way, the effects of the blade rotation can be explained with the help of the frame of reference, allowing for explicit modelling of the impeller geometry. [36,38] A number of studies on the impeller configuration have been reported, especially the Ruston turbine which has the lowest power number. The impeller type, configuration, size, and placement position have obvious effects on the power number or other flow field physical quantities.…”
Section: Rotation Modelmentioning
confidence: 99%
“…The height of the flotation column determines the retention time of the slurry, which directly affects the efficiency of the mineralization. Unlike the ordinary flotation column, the FCSMC has integrated a more efficient mineralization method, such as cyclonic separation and pipe flow mineralization, in view of the gradual deterioration of floatability during the flotation of minerals, and that makes it possible to reduce the column height . Therefore, the hydrodynamic behavior is particularly important for the separation of the FCSMC.…”
Section: Introductionmentioning
confidence: 99%